On Complete Moment Convergence for Randomly Weighted Sums of NSD Random Variables (Journal of Mathematical Study, 2019)
In this paper, we investigate the complete moment convergence and complete convergence for randomly weighted sums of negatively superadditive dependent (NSD, in short) random variables. The results obtained in the paper generalizethe convergence theorem for constant weighted sums to randomly weighted sums ofdependent random variables. In addition, strong law of large numbers for NSD sequence is obtained.
Keywords: Complete moment convergence; randomly weighted; negatively superadditive dependent random variables.